1999
DOI: 10.1172/jci4230
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte infection by the granulocytic ehrlichiosis agent is linked to expression of a selectin ligand

Abstract: Human granulocytic ehrlichiosis (HGE) is a newly recognized tickborne infection of humans (1-3). HGE is a febrile illness characterized by reductions in blood leukocyte and platelet counts and the presence of colonies of infecting organisms (morulae) proliferating within cytoplasmic vacuoles of circulating neutrophils. No other organism is known to replicate within human granulocytes. Our laboratory recently isolated and propagated the causative agent of this disease using the human promyelocytic leukemia cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
124
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(137 citation statements)
references
References 33 publications
12
124
1
Order By: Relevance
“…2D). Chelation of divalent cations with EDTA had no effect on binding, as observed previously (25) for bacterial binding to HL-60 cells. This contrasts with the Ca 2ϩ -dependent binding of selectins to PSGL-1 and other sLe x -capped glycoconjugates (11,12).…”
Section: A Phagocytophilum Binds To a Glycopeptide Modeled After Thesupporting
confidence: 83%
See 1 more Smart Citation
“…2D). Chelation of divalent cations with EDTA had no effect on binding, as observed previously (25) for bacterial binding to HL-60 cells. This contrasts with the Ca 2ϩ -dependent binding of selectins to PSGL-1 and other sLe x -capped glycoconjugates (11,12).…”
Section: A Phagocytophilum Binds To a Glycopeptide Modeled After Thesupporting
confidence: 83%
“…Binding of A. phagocytophilum to human myeloid HL-60 cells requires cell surface sialylation and correlates with expression of FTVII (25). Moreover, mAbs to N-terminal epitopes on human PSGL-1 inhibit binding of A. phagocytophilum to human neutrophils or HL-60 cells (26).…”
mentioning
confidence: 99%
“…The HGE agent completely inhibited O 2 Ϫ release by neuraminidasetreated neutrophils in the presence or absence of PMA. Unlike the case for HL-60 cells (10), treatment of neutrophils with neuraminidase did not inhibit infection by the HGE agent. Following 16 h of incubation, distinct morulae (microcolonies of ehrlichiae) were present in 6.2% Ϯ 0.5% and 4.1% Ϯ 0.5% (n ϭ 3) of nontreated and treated neutrophils, respectively.…”
Section: Upon Exposure To Neutrophils the Hge Agent Did Not In-contrasting
confidence: 65%
“…A recent study by Goodman et al (10) has shown that treatment of HL-60 cells with neuraminidase prevents both binding and infection by the HGE agent. To examine whether an external sialic acid on the neutrophil surface is required for inhibition of O 2 Ϫ release by the HGE agent, neutrophils were pretreated with neuraminidase prior to incubation with the HGE agent.…”
Section: Upon Exposure To Neutrophils the Hge Agent Did Not In-mentioning
confidence: 99%
“…One potential direct mechanism by which bacterial contact or infection may result in CD11b/CD18 up-regulation is via PSGL-1. It was recently demonstrated that the aoHGE directly infects human neutrophils via receptor-mediated endocytosis using PSGL-1 as a receptor (Goodman et al, 1999;Herron et al, 2000). As stimulation of PSGL-1 activates mouse neutrophils, it is indeed possible that binding of aoHGE is an initiating event that leads to cellular activation and increased expression of CD11b/CD18 on the host cell surface (Blanks et al, 1998).…”
Section: Discussionmentioning
confidence: 99%